Pathogenic, immunologic, and clinical aspects of sepsis - update 2016 - Uhle, Florian; Chousterman, Benjamin G.; Grützmann, Robert; Brenner, Thorsten; Weber, Georg (Expert Review of Anti-Infective Therapy, 2016)
Sepsis is a major cause of death worldwide but its orchestrating components remain incompletely understood. On the one hand, development of sepsis results from an infectious focus that cannot be controlled by the immune system, but on the other, responding immune cells that can eliminate the infection inflict damage to the host by contributing to complications such as endothelial leakage, septic shock, and multiorgan failure.In this review we give a comprehensive overview of how sepsis occurs, which exogenous and endogenous factors might affect the immune-pathophysiological course of sepsis and finally how this knowledge translates into up-to-date definitions and therapeutic approaches. Expert commentary: Although new immunological mechanisms altering the course of sepsis have been identified recently, future research needs to address the limitations of experimental approaches, redirect the research focus into translational approaches, and finally evaluate personalized treatment strategies.
EVALuna2:15252